Naturalne metody wspomagania odporności w walce z koronawirusem - Katarzyna Jankowska; Natalia Suszczewicz (Wiedza Medyczna, 2020)
Since the threat of SARS-CoV-2 coronavirus infection is still real and it is becoming more and more difficult to protect yourself against infection, there is a need to pay attention to body's immune status. An efficient immune system is the basis of a proper anti-infective response. It was noticed in antiquity that only people who survived the disease themselves are suitable for the care of the sick. What can we do to support immunity? It would be best to go through the coronavirus infection as asymptomatic or scanty, create antiviral antibodies and have persistent immunity. This is possible, but only if the immune system is working properly and the co-morbidities are not too aggravating. The functioning of the immune system determines many factors that are independent of us, such as: genetic conditions, age or gender. However, we have a real influence on many factors: physical activity, stress, sleep, diet. Scientific evidence clearly indicates that the right lifestyle translates into the overall health, particularly favorably affecting the immune, respiratory, blood, endocrine, carbohydrate and lipid metabolism. Caring for a healthy lifestyle, we can reduce the risk of serious infections, including SARS-CoV-2. We have no major impact on the function of the thymus or bone marrow, where immunologically competent cells are produced, but we do have a significant impact on the state of one of the most important organs of the immune system - the intestines. The area of ​​the intestines of an adult is about 300m2, which is why they constitute the main pathway for antigens. The laboratories are developing more and more effective drugs, more and more effective plant protection products. Our immune system must fight against increasingly stronger pathogens, with increasingly stronger pests. Human immunity is decreasing, living conditions on Earth are becoming increasingly difficult. Food is less and less natural, genetically modified, contains more and more tasty additives, and less and less valuable nutrients. Supplementation becomes necessary.The article presents a review of natural methods of supporting immunity with particular emphasis on diet.